Re-Desain Alat Pencacah yang Ergonomis Guna Mempercepat Waktu Proses Produksi Pupuk Cair Organik - Muhammad Ali Imron; Putu Eka Dewi Karunia Wati (SURYA TEKNIKA, 2024)
A chopper is a tool used to chop or crush materials into smaller and finer pieces. In papungan village, a shredding tool is used to chop the materials used for making liquid organic fertilizer, this is because the high cost of chemical fertilizers is one of the reasons farmers switch to organic fertilizers. The shredding tool that has been designed has several obstacles, one of which is the most prominent, namely when chopping fibrous materials, the machine falters and even dies, so it is necessary to re-design the tool. The purpose of this re-design is to solve the problems experienced by the tool. There are several changes and additions to the tool to solve problems and improve tool performance. The redesigned tool can speed up production time 58,6%/2,4x and the resulting chopping is smoother than the previous tool.